Pengaruh Kemampuan Kerja Terhadap Prestasi Kerja Pegawai Pada Dinas Perumahan Dan Kawasan Permukiman Kabupaten Bima - Muhammad Amar Makmun; Jaenab Jaenab (Tirtayasa Ekonomika, 2020)
The purpose of this study is to find out and analyze the Effect of Significant Work Ability on Employee Job Performance at the Bima Regency Housing and Settlement Office. The type of research used is associative, with a sample of 68 respondents. The sampling technique used was purposive sampling. Data collection using a questionnaire with a Likert measurement scale. Data analysis methods used are validity test, reliability test, simple linear regression, simple correlation, determination test and t test (two parties). The results of this study concluded that work ability did not have a significant effect on work performance in the Bima Regency Housing and Settlement Office, where the t value was 1.356 smaller than the t table value of 1.996 (1.356 <1.996) with a significance value of 0.180 greater from 0.05 (0.180> 0.05).